Discussion about math, puzzles, games and fun.   Useful symbols: ÷ × ½ √ ∞ ≠ ≤ ≥ ≈ ⇒ ± ∈ Δ θ ∴ ∑ ∫ • π ƒ -¹ ² ³ °

You are not logged in.

## Post a reply

Write your message and submit
|
Options

## Topic review (newest first)

Milos
2005-05-14 23:09:48

n e time

MathsIsFun
2005-05-13 20:50:01

Thanks, Milos ...

TEAMWORK !

Milos
2005-05-13 20:20:21

2AB = 2x - 1  ^2
4A^2B^2=4x^2 - 2x + 1
Now: A=sqr(x+1); B=sqr(x-1)
4x^2-4=4x^2 - 4x + 1
then:
4x=5
x=5/4
It was easy, because administrator has finished the difficult part.

MathsIsFun
2005-05-13 10:45:49

Cool ... I will leave it for someone else then ...

Good luck.

im really bored
2005-05-13 10:44:13

I know, but i can handle that.  It was just my approach that was getting me. I was trying to go at it in a more complicated way

MathsIsFun
2005-05-13 10:41:38

Well, we still aren't ALL the way there ... we still have 2AB to solve

im really bored
2005-05-13 10:33:45

Wow it makes alot more sense putting it that way, I was tying to aproach it from some other way, which turned out horrible.Thanks for the help I understand it now

MathsIsFun
2005-05-13 10:30:52

For simplicity, let's call sqrt(x+1) "A" and sqrt(x-1) "B"

You have: (A+B)/(A-B) = (4x-1)/2

Multiply both sides by (A+B)*(A-B):    (A+B)*(A-B) * (A+B)/(A-B) = (A+B)*(A-B) *  (4x-1)/2

Cancel: (A+B)^2 = (A+B)*(A-B) *  (4x-1)/2

Expand: A^2 + 2AB + B^2 = (A^2 - B^2) * (4x-1)/2

Substitute A^2 = (x+1) and B^2 = (x-1): (x+1) + 2AB + (x-1) = ((x+1) - (x-1)) * (4x-1)/2

Simplify: 2x + 2AB = 2 * (4x-1)/2

More: 2x + 2AB = 4x - 1

More: 2AB = 2x - 1

MathsIsFun
2005-05-13 09:54:16

I will work on it ...

I think the trick will be to multiply by [sqrt(x+1)-sqrt(x-1)]^2

Anyway, let's try and see how far we get

[sqrt(x+1)-sqrt(x-1)] * [sqrt(x+1)+sqrt(x-1)] =  [sqrt(x+1)-sqrt(x-1)]^2 * (4x-1)/2

sqrt(x+1) * sqrt(x+1) + sqrt(x+1) * sqrt(x-1) - sqrt(x-1) * sqrt(x-1) - sqrt(x-1) * sqrt(x-1) = ...

(x+1) + (terms cancel each other) - (x-1) = ...

2 =  [sqrt(x+1)-sqrt(x-1)] *  [sqrt(x+1)-sqrt(x-1)] *  (4x-1)/2

2 = [sqrt(x+1) * sqrt(x+1) - sqrt(x+1) * sqrt(x-1) - sqrt(x-1) * sqrt(x+1) + sqrt(x-1) * sqrt(x-1)] *  (4x-1)/2

2 = [(x+1) - 2 * sqrt(x+1) * sqrt(x-1) + (x-1)]  * (4x-1)/2

2 = [2x - 2 * sqrt(x+1) * sqrt(x-1) ] * (4x-1) / 2

4 = [2x - 2 * sqrt(x+1) * sqrt(x-1) ] * (4x-1)

Hmmm ... that helped a bit, let's try it again but using [sqrt(x+1)+sqrt(x-1)] * [sqrt(x+1)-sqrt(x-1)]

im really bored
2005-05-13 09:34:40

I'm having trouble doing this problem:

solve for x

(square root of ( x + 1) + (square root of (x - 1)        4x - 1
_________(divided by)_____________________   =  ___(divided by)___
(square root of ( x + 1) - (square root of (x - 1)             (2)

## Board footer

Powered by FluxBB